TINGKAT KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN KEFARMASIAN DI APOTEK WILAYAH KECAMATAN COLOMADU KOTA KARANGANYAR - Amal Fadholah; Zahra Hanifah Baharriski; Lija Oktya Artanti (Pharmasipha: Pharmaceutical Journal of Islamic Pharmacy, 2021)
The pharmacy is a pharmaceutical service facility where the pharmacist practices pharmacy. The professionalism of the performance of a pharmacist in a service is very influential in improving the quality of public health. If the service performance provided can rich patient expectation, it will automatically grow a good level of patient satisfaction. This study aims to determine and evaluate the level of patient satisfaction by assessing the 5 dimensions of pharmaceutical services at pharmacies that cover facilities, reliability, responsiveness, assurance, and empathy. Evaluation of the quality of pharmaceutical service in pharmacies is very necessary so that pharmacists can continuously make improvements both in terms of service products or services. This study was included in a non-experimental descriptive study, with a Cross-Sectional data collection model. The total of samples is 140 respondents taken from 5 pharmacies located in the Colomadu District Region Karanganyar City. Overall the percentage of patient satisfaction on the quality pharmaceutical service shows a satisfactory interpretation of 78.86%. The highest gap of the 5 dimensions is found in the tangible dimension and the responsiveness dimension is -0.08. the results of the Importance-Performance Matrix Analysis show that the majority of the overall statement items are in quadrant II and III with the meaning that some pharmaceutical services need to be maintained (keep up the good work) and some services have shown good performance that does not need to be prioritized (low priority).